The Morpho-Syntax of Clausal Negation in Rural Jordanian Arabic - AL-DEAIBES, MUTASIM (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
In this paper, I argue that the Neg particles head their projections, and the negation in a hierarchical representation occurs between TP and VP. In future tense, I argue that the Aux can move to the Neg head just to pick the negation and then the negative particle and the Aux moves to T. I also show that speakers of RJA use different negation constructions depending on the structure and tense of the sentence. For example, the negative particle ma is a preverbal particle used with present and past verbs evenly. The negative particleÂ ma¦-ƒ is a pre and post-verbal particle where ma is a proclitic and -ƒ is an enclitic. This particle is used with present verbs and past verbs. However, when used with present tense verbs, the proclitic ma becomes optional, whereas with past tense verbs the deletion of the procliticÂ maÂ results in an ungrammatical sentence. As for copular sentences, the particle miƒ is used to negate verbless copular sentences where there is a covert present tense verb. But, when the copular sentence is formed via a past tense verb, miƒ is no longer used. Instead, the negative construction maâ¦-ƒ is used.